De la guerre civile aux droits ethnolinguistiques : le cas du Nicaragua - Bénédicte Pivot (Lengas)
Taking the case of the civil war between the Sandinista revolutionary government and the Contra (Nicaragua, 1979-1989), this article offers a reflection about the impact of war on language policies and sociolinguistic (re)configurations. Effects on social groups of recognition by war politics of the linguistic rights of previously unrecognized minorities are highlighted by the way linguistic landscape and social relations at regional, national and ultimately international are redesigned. If these effects are effective in various fields related to ethnic and cultural identity, the example concerns more specifically the consequences on the education system questioning the way to manage the place of languages ​​in schools.